The best of Dagmay 2 2010-2012 - Cruz, Jhoanna Lynn B.; Bengan, John; Cruz, Jhoanna Lynn B.; Cimafranca, Dominique Gerald M.; Pagusara, Don; National Commission on Culture and the Arts (Philippines). (Manila National Commission for Culture and the Arts, 2016)
A collection of fiction, poetry, drama, and creative nonfiction from more than 200 young Davaoeño and Mindanaoan authors.
Chiefly in English, some articles in Cebuano and Tagalog.
UCASM-2466 (UCASM002466) donated by NCCA
Keywords: Philippine literature -- 20th century; Philippine literature -- Philippines -- Davao City